Diversity in the space physics community: an overview of collaborative efforts led by The University of Alabama in Huntsville - Mehmet S. Yalim; Gary P. Zank; Gary P. Zank; Laura Provenzani; Douglas Spencer; Katie Howatson (Frontiers in Astronomy and Space Sciences, 2023)
The field of Space Physics has significant recruitment potential. Almost everyone has been fascinated by space in one way or another since their early childhood. From this perspective, Space Physics might be expected to exhibit considerable diversity as a discipline. Regrettably, as in many STEM fields, the reality is quite different. Numerous reasons have been advanced about why the reality and the expectation diverge but one observation we have made over the years stands out, and, that is, that when students are given the opportunity, they are very eager to learn about Space Physics and enthusiastic about working on space physics projects. At The University of Alabama in Huntsville, we have developed a series of outreach programs, including summer programs, that are aimed at bringing students not typically exposed to space physics into the Space Physics community through working on real research projects that have the potential to produce journal publication results. These programs have been very effective in creating interest in Space Physics and have led to the recruitment of students that have been underrepresented historically into our research programs. In this paper, we summarize the various summer programs that the Center for Space Plasma and Aeronomic Research and Department of Space Science at The University of Alabama in Huntsville have been organizing in Space Physics for years and how these programs have contributed to increasing diversity in the field.